Fundamentação das decisões judiciais: elementos para superação do conceito de motivação das decisões a partir da análise comparativa da atuação jurisdicional da Supreme Court e dos tribunais brasileiros - Thiago Carlos de Souza Brito (2017)
The purpose of this thesis was to demonstrate, using the comparative method, the motivation of the judicial decisions handed down by the Supreme Court of the United States and the Brazilian Courts, with the purpose to reconstruct the method adopted by the magistrates to motivate. The first part of the paper deals with the historical mutation of the motivation, from its Roman origin to its modern statute of the CPC of 2015. Next, the theoretical aspects of the motivation are demonstrated, related to its purpose, requirements, method and content. Next, it also analyzes the arguments regarding the lack of motivation by the Brazilian magistrates. The second part examines two changes in the legal theory, concerning the judicial activism and the use of precedents, which justify the modification of the method of justification of the judicial decision.The third part analyzes the method of motivation of judicial decisions issued by the Supreme Court of the United States of America, through the empirical verification of cases selected according to the methodology defined in this work. The fourth part presents the results of the empirical survey concerning the method of motivation used by the previously selected Brazilian Courts, according to the same methodology adopted in the third part of the study. The fifth part of the paper addresses the issues identified in the justification of the decisions analyzed by the Brazilian courts, indicating practices that impede correct justification by the judges.The sixth part, finally, elaborates some solutions to the problems identified in the fifth part of the work, with the purpose to overcoming the method used by judges of the Brazilian Judiciary.